Strengthen PSNP4 Institutions and Resilience (SPIR), Ethiopia: Midline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
The Strengthen PSNP4 Institutions and Resilience (SPIR) Development Food Security Activity (DFSA) in Ethiopia was a five-year project (2016-2021) supporting the implementation of the fourth phase of the Productive Safety Net Programme (PSNP4) as well as providing complementary livelihood, nutrition, gender, and climate resilience activities to strengthen the program and expand its impacts. IFPRI conducted an experimental, quantitative impact evaluation of SPIR designed to measure the causal impact of multisectoral “graduation model” packages of interventions for improving outcomes in several domains, including livelihoods, food security, child nutrition, women’s empowerment, mental health, and intimate partner violence (IPV). The impact evaluation used a clustered RCT design to learn about the effect of different combinations of the SPIR interventions on the well-being of PSNP4 households. These packages were combined into multisectoral graduation model programs and randomized at the kebele level into four treatment arms. The evaluation sample comprised of 192 kebeles and 15 woredas in the Amhara and Oromia regions. The baseline survey was conducted from March to May 2018, and 3,314 households were interviewed. The fieldwork for the midline survey took place between August and October of 2019, and a supplemental sample of 748 households was added to the original sample to have more children under the age of 2 years, putting the total sample interviewed at the midline to 3,968. The endline survey was conducted between February and April of 2021, and the final sample interviewed at the endline was 3,912 households. The survey instrument had three parts – household survey, female survey, and male survey, and was broadly similar across rounds, while some modules changed.